Climate change and agriculture: Farmer adaptation to extreme heat - Fernando M. Aragón; Francisco Oteiza; Juan Pablo Rud (Institute for Fiscal Studies (IFS), 2018)
This paper examines how farmers adapt, in the short-run, to extreme heat. Using a production function approach and micro-data from Peruvian households, we find that high temperatures induce farmers to increase the use of inputs, such as land and domestic labor. This reaction partially attenuates the negative effects of high temperatures on output. We interpret this change in inputs as an adaptive response in a context of subsistence farming, incomplete markets, and lack of other coping mechanisms. We use our estimates to simulate alternative climate change scenarios and show that accounting for adaptive responses is quantitatively important.
Keywords: O13; O12; Q12; Q15; Q51; Q54; 330